All the Lonely People: An Integrated Review and Research Agenda on Work and Loneliness - McCarthy, Julie M.; Erdogan, Berrin; Bauer, Talya N.; Kudret, Selin; Campion, Emily (Journal of Management, 2026)
Decades of studies spanning multiple disciplines have provided insight into the critical role of loneliness in work contexts. In spite of this extensive research, a comprehensive review of loneliness and work remains absent. To address this gap, we conducted a multidisciplinary review of relevant theory and research and identified 213 articles reporting on 233 empirical studies from management, organizational psychology, sociology, medicine, and other domains to uncover why people feel lonely, how different features of work can contribute to feelings of loneliness, and the implications of employee loneliness for organizational settings. This enabled a critical examination of the distinct conceptualizations and operationalizations of loneliness that have been advanced and the theories underpinning this scholarship. We developed a comprehensive conceptual model that integrates cognitive discrepancy theory, the affect theory of social exchange, and evolutionary theory. This model elucidates the core antecedents, mediators, outcomes, moderators, and interventions forming the nomological network of work related loneliness, including cross-level influences within teams and among leaders. Our review also identifies a number of promising areas for future inquiry to improve our understanding and measurement of loneliness, the process of experiencing and managing loneliness in the workplace, and potential interventions to reduce it. Finally, we provide tangible guidance for organizations and practitioners on how to address and mitigate employee loneliness. Ultimately, our review underscores the complex nature of loneliness and work and establishes a foundation for advancing both scholarly discourse and organizational practices in this critical domain.